2012
DOI: 10.1107/s0108768112030091
|View full text |Cite|
|
Sign up to set email alerts
|

Crystallographic input data for (001)-, (110)- and (111)-oriented superlattices

Abstract: General aspects concerned with (001)-, (110)- and (111)-oriented superlattices (SLs) have been investigated. In particular, the symmetry of these systems have been derived and given in detail. As a test, the obtained data have been utilized to calculate electronic structures and gaps of a standard GaAs/AlAs system using an accurate version of the first principle full potential linear muffin-tin orbital (FPLMTO) method based on a local-density functional approximation (LDA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Two cases will be used: SL s grown along with the (001) and (110) directions. While the structural properties of (001)-oriented semiconductor SL s have been studied in great detail by using first-principles methods, there is not a comparable amount of information about the properties of (110)-oriented SL s [12]. It is reported that (110) oriented SL s exhibit considerably different characteristics compared to those grown along the (001) direction.…”
Section: Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two cases will be used: SL s grown along with the (001) and (110) directions. While the structural properties of (001)-oriented semiconductor SL s have been studied in great detail by using first-principles methods, there is not a comparable amount of information about the properties of (110)-oriented SL s [12]. It is reported that (110) oriented SL s exhibit considerably different characteristics compared to those grown along the (001) direction.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…It is found in literature many studies showing InN/GaN system make the design of various InN-based heterostructure devices possible [6,11]. Indeed, its bandgap can cover the whole solar spectrum solely by changing the number of GaN monolayers in InN/GaN SL s [12,15]. It is well known that crystal orientations have a significant impact on their properties and their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Equations (13)-(18) in the paper by Touaa & Sekkal [(2012), Acta Cryst. B68, 378-388] are corrected.…”
mentioning
confidence: 99%